2021
DOI: 10.5423/ppj.oa.02.2021.0018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Alternaria Species Associated with Watermelon Leaf Blight in Korea

Abstract: Alternaria leaf blight is one of the most common diseases in watermelon worldwide. In Korea, however, the Alternaria species causing the watermelon leaf blight have not been investigated thoroughly. A total of 16 Alternaria isolates was recovered from diseased watermelon leaves with leaf blight symptoms, which were collected from 14 fields in Korea. Analysis of internal transcribed spacer (ITS) region, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and RNA polymerase II second largest subunit (RPB2) were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Rodrigues et al [34] demonstrated that A. tomatophila was able to infect not only tomato but also potato plants, experimental inoculation tests showed brownish lesions on inoculated potato leaves. A. alternata has been identified to be pathogen causing citrus brown spot and watermelon leaf blight [35,36]. Its diseased symptoms on citrus are brown to black lesions surrounded by a yellow halo, and leaf drop if severely infected [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al [34] demonstrated that A. tomatophila was able to infect not only tomato but also potato plants, experimental inoculation tests showed brownish lesions on inoculated potato leaves. A. alternata has been identified to be pathogen causing citrus brown spot and watermelon leaf blight [35,36]. Its diseased symptoms on citrus are brown to black lesions surrounded by a yellow halo, and leaf drop if severely infected [35].…”
Section: Discussionmentioning
confidence: 99%
“…Its diseased symptoms on citrus are brown to black lesions surrounded by a yellow halo, and leaf drop if severely infected [35]. In watermelon, A. alternata induced dark brown leaf spot lesions similar to the symptoms that appeared in citrus [36]. Moreover, it was reported that Alternaria species can infect more than one host plant [37].…”
Section: Discussionmentioning
confidence: 99%